Mining for allelic gold: finding genetic variation in photosynthetic traits in crops and wild relatives - Sharwood, Robert E.; Quick, W. Paul; Sargent, Demi; Estavillo, Gonzalo M.; Silva-Perez, Viridiana; Furbank, Robert T. (Oxford University Press, 2022)
Improvement of photosynthetic traits in crops to increase yield potential and crop resilience has recently become a major breeding target. Synthetic biology and genetic technologies offer unparalleled opportunities to create new genetics for photosynthetic traits driven by existing fundamental knowledge. However, large ‘gene bank’ collections of germplasm comprising historical collections of crop species and their relatives offer a wealth of opportunities to find novel allelic variation in the key steps of photosynthesis, to identify new mechanisms and to accelerate genetic progress in crop breeding programmes. Here we explore the available genetic resources in food and fibre crops, strategies to selectively target allelic variation in genes underpinning key photosynthetic processes, and deployment of this variation via gene editing in modern elite material.